(untitled) (World Bulletin of Management and Law, 2022)
In the presented article, interactive methods of teaching students are considered. Joint activity means that everyone makes his own special individual contribution, in the course of work there is an exchange of knowledge, ideas, ways of activity. Particular attention in the work was paid to the development in each student individually of creative abilities and the ability to think outside the box